132 STANDARDIZED NASAL CANNULA ORDER SETS DECREASE OXYGEN DAYS IN INFANTS < 1, 500 G. Issue 1 (1st January 2007) - Nelson, M.; Zagorski, J.; Regan, D.; McGovern, F.
Abstract : A standardized approach to weaning supplemental nasal cannula oxygen more quickly and consistently was undertaken in an attempt to minimize oxygen exposure in infants convalescing in the NICU at Emanuel Children's Hospital. All nasal cannula support is administered with blended oxygen at this institution, so two parameters can be weaned: flow and oxygen tension. There is often confusion among the staff as to which parameter to wean consistently, leading to prolonged days on supplemental oxygen. Standardized order sets with weaning guidelines illustrated by flow diagram were developed. A 3-month pilot study was undertaken. All infants admitted to the NICU requiring nasal cannula oxygen were eligible. Infants with cyanotic heart disease were excluded. Data were prospectively collected on infants managed with nasal cannula order sets. Infants in the experimental group (NCO) were then compared with infants placed on nasal cannula without order sets (controls) from the same time period the year before. Infants were stratified by birth weight (≤ 1, 500 g ≥ 1, 501 g). There were 31 patients in the control group and 23 patients in the NCO group. There were 12 control patients ≤ 1, 500 g and 11 NCO patients ≤ 1, 500 g. Data were analyzed using Student t tests ( p < .05 significant). Groups were well matched for demographics (under 1, 500 g group: 6/12 male controls vs 5/11 male NCO; median bwt = 1, 080 g control vs 1, 000 g NCO; mean GA 28.4 wk ± 2.7 wk control vs 28.5 wk ± 2.0 wk). Infants under 1, 500 g were also well matched for number who received antenatal steroids (9/12 controls vs 9/11 NCO). Results: Nasal cannula oxygen days were much lower for the NCO group (4.5 d ± 2.6 d) versus the control group (8.4 d ± 4.8 d) for all infants in the study (big and small), but the difference was not statistically significant ( p < .06). There was no significant difference for oxygen days (2.1 d ± 1.4d NCO vs 3.5 d ± 2.8 d control) for the large infants ( p < .11). Upon comparison of small infants (≤ 1, 500 g), a strongly significant difference was found between groups (7.2 d ± 3.4 d NCO vs 15.9 d ± 5.2 d controls; p < .02). These preliminary data indicate that days on nasal cannula oxygen may be significantly shortened if standardized nasal cannula order sets are used to direct consistent weaning.